2015
DOI: 10.3390/ijms16047334
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Efficient Electroporation Method for Iturin A-Producing Bacillus subtilis ZK

Abstract: In order to efficiently introduce DNA into B. subtilis ZK, which produces iturin A at a high level, we optimized seven electroporation conditions and explored an efficient electroporation method. Using the optimal conditions, the electroporation efficiency was improved to 1.03 × 107 transformants/μg of DNA, an approximately 10,000-fold increase in electroporation efficiency. This efficiency is the highest electroporation efficiency for B. subtilis and enables the construction of a directed evolution library or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…In this study, we used D-sorbitol or sucrose as an osmoprotectant. D-Sorbitol was previously used for electroporating B. subtilis (29,47), and in prior work, our lab used D-sorbitol as an osmoprotectant to show that C. difficile and Paraclostridium bifermentans mechanosensing channels are involved in the release of dipicolinic acid from the spore core during germination (48). Though C. difficile R20291 grown in sorbitol-containing medium could be transformed by electroporation, we could not obtain any transformants from the C. difficile CD630 or JSC10 strain.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, we used D-sorbitol or sucrose as an osmoprotectant. D-Sorbitol was previously used for electroporating B. subtilis (29,47), and in prior work, our lab used D-sorbitol as an osmoprotectant to show that C. difficile and Paraclostridium bifermentans mechanosensing channels are involved in the release of dipicolinic acid from the spore core during germination (48). Though C. difficile R20291 grown in sorbitol-containing medium could be transformed by electroporation, we could not obtain any transformants from the C. difficile CD630 or JSC10 strain.…”
Section: Discussionmentioning
confidence: 91%
“…Fragility of the cell wall enhances transformation efficiency (45). Glycine is the most common additive used for electroporating B. subtilis (29), Bacillus mycoides (46), and Clostridium pasteurianum (35). We observed that C. difficile requires glycine to generate transformable cells; the absence of glycine did not produce colonies after electroporation.…”
Section: Discussionmentioning
confidence: 99%
“…in a study of the transformation of E. coli spheroplasts through the chemical CaCl 2 method[23] and in several other studies with different bacteria. [142425262728] However, some researchers reported that cell-wall-weakening either had no effect on the transformation frequency. [29] It seems that type of bacteria, cell-wall-weakening agents for spheroplast formation, and the transformation method used should be affected on the result.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression plasmids were introduced into B. subtilis ZK0 by electroporation (Zhang et al . ). Before fermentation, the strain was activated on LB solid medium at 37°C for 24 h and inoculated into 25 ml of LB liquid medium in a shaker at 30°C and 150 g for 18 h. Then, 5 ml of seed culture was added to 45 ml of the fermentation medium (16 g of glucose, 0·1 g of yeast extract, 3·7 g of KH 2 PO 4 , 52·1 g of soy peptone and 7·3 g of MgSO 4 ·7H 2 O per litre of water, pH 8·0) with 1 mmol l −1 IPTG.…”
Section: Methodsmentioning
confidence: 97%